2015
DOI: 10.7567/apex.8.054101
|View full text |Cite
|
Sign up to set email alerts
|

1.8 mΩ·cm2vertical GaN-based trench metal–oxide–semiconductor field-effect transistors on a free-standing GaN substrate for 1.2-kV-class operation

Abstract: In this paper, we report on 1.2-kV-class vertical GaN-based trench metal–oxide–semiconductor field-effect transistors (MOSFETs) on a free-standing GaN substrate with a low specific on-resistance. A redesigned epitaxial layer structure following our previous work with a regular hexagonal trench gate layout enables us to reduce the specific on-resistance to as low as 1.8 mΩ·cm2 while obtaining a sufficient blocking voltage for 1.2-kV-class operation. Normally-off operation with a threshold voltage of 3.5 V is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
232
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(249 citation statements)
references
References 22 publications
(33 reference statements)
3
232
0
Order By: Relevance
“…For the trench structure, they used a combination of dry etching and subsequent wet etching with tetramethylammonium hydroxide. Recently, Oka et al 6 also reported a trench-type . In these cases, it was expected that the insulated gate on the dry-etched p-GaN surface could realize device operation with an inverted channel.…”
Section: à2mentioning
confidence: 98%
“…For the trench structure, they used a combination of dry etching and subsequent wet etching with tetramethylammonium hydroxide. Recently, Oka et al 6 also reported a trench-type . In these cases, it was expected that the insulated gate on the dry-etched p-GaN surface could realize device operation with an inverted channel.…”
Section: à2mentioning
confidence: 98%
“…Similar devices can be realized with all-AlGaN or Ga 2 O 3 , with appropriate current blocking techniques, to access higher operating voltages. [217][218][219][220] However, the CAVET suffers from its own problems; for example, it requires a number of etch-and-regrowth steps which to date have resulted in buried pn junctions with excessive leakage current, due to traps introduced at the etched surfaces. Nonetheless, normally-off devices may be easier to realize in a CAVET than in a vertical JFET, again due to the precise doping and layer thickness control afforded by epitaxy as opposed to lithography and implantation.…”
Section: Methodsmentioning
confidence: 99%
“…4,5,[27][28][29] Among the various methods for the growth of freestanding GaN substrates, hydride-vaporphase epitaxy (HVPE) is the most well established, and wafers with diameters of 2-in. or more have been prepared and used in the mass production of optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%